Trinitarian spirituality: Relational and missional - Reimer, Johannes (HTS Teologiese Studies / Theological Studies, 2019)
In recent years, Orthodox views on trinitarian theology have enriched the Evangelical discourse on mission and spirituality. Very few sources of Orthodox thought have influenced this discourse more than the hesychastic beliefs and praxis of the medieval Russian spiritual leader Sergii of Radonezh, as expressed by his disciple, the famous icon painter Andrey Rublev. This article discusses the theology of Rublev, follows its spirituality and explores a correlation between the inner-trinitarian spirituality and God´s mission, establishing what is called a trinitarian cycle of the missio Dei.
free
Keywords: CHRISTIAN spirituality; Correlation between mission and spirituality; DOCTRINAL theology; GOD in Christianity; HESYCHASM; Hesychasm; Mission of God; ORTHODOX Eastern mysticism; Russian Orthodox Theology; TRINITY; Trinitarian theology; Trinity